A CASE OF RENAL DISEASE IN HIV INFECTED PATIENT - Vina Septiani, Ni Made; Sudhana, I Wayan (E-Jurnal Medika Udayana; vol 2 no 11 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Kidney diseases in human immunodeficiency virus (HIV ) infected patients has been been fourth leading cause of death after sepsis, pneumonia, and liver disease . HIV -associated nephropathy ( HIVAN) is the most common . We report a case , a male patient , 48 years , who experienced shortness of breath , cough and intermittent fever and has been reported as HIV positive , without previous antiretroviral treatment and last CD4 + count is 89 cells/mm3. There are elevated BUN and SC from day to day during treatment and proteinuria +2 as a sign of kidney disease with normal blood pressure and there was no edema . Patients given an antibiotic and ACE inhibitors as antiproteinuria . Patients with suspicion of HIVAN in this case can progress very rapidly and causes progressive decline in renal function . Prognosis of patients with HIVAN if not handled properly will develop end stage renal disease ( ESRD) in 1-4 months and had a mortality rate 4.7 times higher than HIV patients without renal impairment . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Renal diseases, human immunodeficiency virus infection, HIVAN